Effect of the Microenvironment on Mesenchymal Stem Cell Paracrine Signaling: Opportunities to Engineer the Therapeutic Effect - Kusuma, Gina D; Carthew, James; Lim, Rebecca; Frith, Jessica E (Stem cells and development, 2017)
Cues from the extracellular environment, including physical stimuli, are well known to affect mesenchymal stem cell (MSC) properties in terms of proliferation and differentiation. Many therapeutic strategies are now targeting this knowledge to increase the efficacy of cell therapies, typically employed to repair tissue functions in the event of injury, either by direct engraftment into the target tissue or differentiation into mature tissues. However, it is now envisioned that harnessing the repertoire of factors secreted by MSCs (termed the secretome) may provide an alternate to these cell therapies. Of current interest are both direct protein secretions and two major subpopulations of bioactive extracellular vesicles (EVs), namely exosomes and microvesicles. EVs released by MSCs are reflective of their cells of origin, able to impact upon the activities of other cells in the local microenvironment, making the rational design of MSC paracrine activities an encouraging strategy to reproducibly modulate cell therapies. The precise mechanisms by which the secretome is modulated by the microenvironment, however, remain elusive. Controlling MSC growth conditions with oxygen tension, growth factor composition, and mechanical properties may serve to directly influence paracrine activity. Our growing understanding implicates components of the mechanotransduction machinery in translating both mechanical and chemical cues from the environment into alterations in gene regulation and varied paracrine activity. As technologies are developed to manufacture MSCs, advances in bioengineering and novel insight of how the extracellular environment affects MSC paracrine activity will play a pivotal role in the generation of widespread, successful, clinical MSC therapies.